Proceso de atención nutricional a paciente femenino de 4 años de edad con caries dental y desnutrición crónica. - Solano Farro, Digna Elena (2022)
A leading cause of malnutrition in children is inadequate nutrition or excessive consumption of foods containing empty calories and simple sugars, both of which affect children's nutritional status and oral health. This clinical case is a 4-year-old female patient with caries and chronic malnutrition, who underwent a nutritional care process, with the aim of establishing a nutritional plan according to the needs of the patient. The nutritional care process was applied to the patient through anthropometric, biochemical, clinical and dietary evaluation, where it reflected: P/E -2 DE, T/E -3 DE, low biochemical data such as hemoglobin, hematocrit, red blood cells, albumin and prealbumin, some micronutrient deficiencies are reflected by clinical signs present in the patient both in the face, eyes, lips and hair, a deficient intake of protein - energy and high in simple sugar that could be evidenced by the 24-hour recall. The evolution of the patient's nutritional status was verified through follow-up, which resulted in a favorable increase in P/E -1 SD and biochemical data in two months. The nutritional recommendations were mentioned to the patient's mother through didactic material, which resulted in improving the patient's diet and oral hygiene habits.